2017
DOI: 10.1111/1750-3841.13591
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Property and Oxidative Stability of Whey Protein Concentrate Multiple Nanoemulsion Containing Fish Oil

Abstract: The objectives of this research were to produce whey protein concentrate (WPC) multiple nanoemulsion (MNE) and to study how whey protein concentration level and antioxidant type affected the physicochemical properties and oxidative stability of fish oil in MNE. The morphological and physicochemical characteristics of MNE were investigated by using transmission electron microscopy and particle size analyzer, respectively. The oxidative stability of fish oil in MNEs was assessed by measuring peroxide value (PV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…In this study, the concentration of hexanal and octanal increased in the puffer fish during storage, which was expected as some aldehydes could be generated from lipid oxidation, for example, hexanal showed in much higher concentrations increase due to the oxidation of both linoleic and linolenic acid and is considered as a good marker for oxidation products of n‐3 and n‐6 fatty acids (Baron et al, ; Frank, Poole, Kirchhoff, & Forde, ). ( E , E )‐2,4‐Heptadienal is an off‐flavor compound and can be considered as a marker of lipid oxidation (Hwang et al, ). The amounts of ( E , E )‐2,4‐heptadienal was significantly ( p < .05) inhibited as storage time, indicating the formation of makers of lipid oxidation was retarded by MAP treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the concentration of hexanal and octanal increased in the puffer fish during storage, which was expected as some aldehydes could be generated from lipid oxidation, for example, hexanal showed in much higher concentrations increase due to the oxidation of both linoleic and linolenic acid and is considered as a good marker for oxidation products of n‐3 and n‐6 fatty acids (Baron et al, ; Frank, Poole, Kirchhoff, & Forde, ). ( E , E )‐2,4‐Heptadienal is an off‐flavor compound and can be considered as a marker of lipid oxidation (Hwang et al, ). The amounts of ( E , E )‐2,4‐heptadienal was significantly ( p < .05) inhibited as storage time, indicating the formation of makers of lipid oxidation was retarded by MAP treatments.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated the protective effect provided by the complex on oxidation of fat by the iron salt. Hwang et al ( 45 ) and Yi et al ( 46 ) also reported the protective effect of WPC on oxidative stability of fish oil as indicated by decrease in the formation of primary and secondary lipid oxidation products. This may be due to the free sulfhydryl groups and aromatic amino acids in the whey proteins, which can act as free radical scavengers contributing to the antioxidant activity.…”
Section: Resultsmentioning
confidence: 96%
“…The oxidative stability of potato crisps and French fries was determined by the formation of peroxide value (PV) and p ‐anisidine value (AV) according to the AOAC method 965.33 and AOCS method Cd 18–90 described by the previous methods . Thus, 2 g of potato products were homogenized in 10 mL chloroform/methanol (2:1, v / v ), then centrifuged at 3000 × g for 20 min.…”
Section: Methodsmentioning
confidence: 99%